2016
DOI: 10.1161/jaha.116.003846
|View full text |Cite
|
Sign up to set email alerts
|

Pain Tolerance in Persons With Recognized and Unrecognized Myocardial Infarction: A Population‐Based, Cross‐Sectional Study

Abstract: BackgroundUnrecognized myocardial infarction (MI) is a prevalent condition associated with a similar risk of death as recognized MI. It is unknown why some persons experience MI with few or no symptoms; however, one possible explanation is attenuated pain sensitivity. To our knowledge, no previous study has examined the association between pain sensitivity and recognition of MI.Methods and ResultsWe conducted a population‐based cross‐sectional study with 4849 included participants who underwent the cold presso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
2
12
0
1
Order By: Relevance
“…Myocardial ischemia stimulates free nerve endings, which usually gives rise to the conscious perception of chest pain [ 28 ]. One possible mechanism for the lack of obvious symptoms of AMI may be increased pain tolerance, which has been described in UMI patients [ 33 ]. However, all patients in the present study had symptoms suggestive of stable angina pectoris for which they have sought medical attention; and hence, were able to perceive chest pain.…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial ischemia stimulates free nerve endings, which usually gives rise to the conscious perception of chest pain [ 28 ]. One possible mechanism for the lack of obvious symptoms of AMI may be increased pain tolerance, which has been described in UMI patients [ 33 ]. However, all patients in the present study had symptoms suggestive of stable angina pectoris for which they have sought medical attention; and hence, were able to perceive chest pain.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects with UMI endured the cold pressor test significantly longer than those with recognized MI, indicating less sensory perception. When stratified according to sex, this association was statistically significant only in women …”
Section: Discussionmentioning
confidence: 97%
“…When stratified according to sex, this association was statistically significant only in women. 39 Another study found that neuropathic pain and polyneuropathy were more common in participants with IGT than in those with NGT. 40 A subsequent study found that individuals with MI with IGT were more likely to have neuropathy than those with NGT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type II may not be sensitive to early myocardial infarction, which is related to a decreased sensitivity to pain. According to research, patients with silent myocardial infarction have a higher pain tolerance than for those experiencing a typical myocardial infarction [ 22 ], and pain sensitivity adjusts and affects the clinical manifestations of the disease [ 23 ]. The difference in central pain regulation has been proposed as one of the causes of painless ischemia.…”
Section: Discussionmentioning
confidence: 99%